Design and Development of a Routing Protocol for Mobile Adhoc Networks - Verma, Anil Kumar (My University, 2008)
The desire to be connected anytime, anywhere, anyhow has led to the development of wireless networks, especially in the area of pervasive and ubiquitous computing. The Mobile Ad hoc NETworks (popularly known as MANETs) are no exception. A wireless ad hoc network is a collection of two or more devices/nodes or terminals with wireless communications and networking capability that communicate with each other without the aid of any centralized administrator. They do not have a fixed topology or infrastructure hence they are also known as infrastructureless networks. Each node in a wireless ad hoc network functions as a host or a router or both. The network topology is in general dynamic and the communication is via an open medium, which is vulnerable. Thus, sophisticated secure routing protocols are needed to safeguard the data against the unauthorized access. The work presented in this thesis is an effort to address the security issues by proposing a new secure routing protocol, termed as SANE-DNA. We consider a routing protocol, namely, Dynamic Source Routing (DSR). The DSR is an on-demand or reactive routing protocol based on the concept of source routing. A pseudo DNA (Deoxyribo Nucleic Acid) based cryptographic algorithm is used in order to secure the MANETs. The pseudo DNA cryptography is a concept inspired from the field of life science and has been extended to the field of MANETs to secure them. Nowadays, DNA is also being considered as a medium for ultrascale computation and for ultra-compact information storage. In the presented work, one potential key application is used known as DNA-based molecular cryptography systems because it provides a much more compact storage medium, and an extremely small amount of DNA suffices even for huge one-time-pads. We have used one-time-pads for DNA-based cryptography and they are found to be unbreakable. The proposed routing protocol has been verified and validated through various simulation scenarios, using synthetically generated data sets. Simulation results demonstrate that the algorithm is secure with marginal overhead. The results have been validated based upon RFC4728 for the DSR protocol. The various parameters considered are: Route Acquisition Time, Average End-to-End Delay (or Mean Overall Packet Latency), Routing Overhead and Throughput (or packet delivery ratio).
Keywords: MANET; Routing Protocols; Security; DNA cryptography